1998
DOI: 10.1172/jci656
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-endothelial interaction is augmented by high glucose concentrations and hyperglycemia in a NF-kB-dependent fashion.

Abstract: We addressed the role of hyperglycemia in leukocyte-endothelium interaction under flow conditions by exposing human umbilical vein endothelial cells for 24 h to normal (5 mM), high concentration of glucose (30 mM), advanced glycosylation end product-albumin (100 microg/ml), or hyperglycemic (174-316 mg/dl) sera from patients with diabetes and abnormal hemoglobin A1c (8.1+/-1.4%). At the end of incubation endothelial cells were perfused with total leukocyte suspension in a parallel plate flow chamber under lami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
264
5
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(295 citation statements)
references
References 49 publications
19
264
5
7
Order By: Relevance
“…[28][29][30] FN gene has both NF-kB and AP-1 binding site on its promoter and may be positively regulated by both transcription factors. [31][32][33][34][35] Data from our present study would suggest that MAPK pathway may upregulate FN via NF-kB and AP-1. However, it is possible that glucose-induced PKC and ET-1 activation may also lead to FN upregulation independent of MAPK activation.…”
Section: Discussionmentioning
confidence: 52%
“…[28][29][30] FN gene has both NF-kB and AP-1 binding site on its promoter and may be positively regulated by both transcription factors. [31][32][33][34][35] Data from our present study would suggest that MAPK pathway may upregulate FN via NF-kB and AP-1. However, it is possible that glucose-induced PKC and ET-1 activation may also lead to FN upregulation independent of MAPK activation.…”
Section: Discussionmentioning
confidence: 52%
“…This radical-scavenging activity could be one of the mechanism of the inhibition of leukostasis observed in this study, because leukocytes in diabetic animals have been reported to be more activated [1,4] and produce more oxygen-derived free radicals [5,6], which induce vascular endothelial dysfunction [7,8,9]. Recent studies demonstrated the increased expression of adhesion molecules under diabetic conditions [2,7,10,26,35]. The interference by gliclazide with the increase in adhesion molecule expression could be another possibility, although it has not been examined in this study.…”
Section: Discussionmentioning
confidence: 76%
“…This effect was independent of increases in serum insulin levels. Several studies have assessed the relation between hyperglycaemia and leucocyte binding to endothelial cells [14][15][16][17]. Although these studies used various experimental conditions and have their own meanings depending on the experimental conditions, most in vivo and in vitro studies have shown that hyperglycaemia induces leucocyte adhesion to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%